Validation of a scale to measure parental psychological empowerment in the vaccination decision - Marta Fadda; Elisa Galimberti; Luisa Romanò; Marino Faccini; Sabrina Senatore; Alessandro Zanetti; Peter Johannes Schulz (SAGE Publishing, 2017)
Background and aims. Parents' empowerment is advocated to promote and preserve an informed and autonomous decision regarding their children' immunization. The scope of this study is to develop and evaluate the psychometric properties of an instrument to measure parents' psychological empowerment in their children's vaccination decision and propose a context-specific definition of this construct. Materials and Methods. Grounding in previous qualitative data, we generated an initial pool of items which was later content and face validated by a panel of experts. A pretest allowed us to reduce the initial pool to 9 items. Convergent and discriminant validity measures included the General Self-Efficacy Scale, a Psychological Empowerment Scale, and the Control Preference Scale. Vaccination-related outcomes such as attitude and intention were also included. Results. Principal Component Analysis revealed a 2-factor structure, with each factor composed of 2 items. The first factor concerns the perceived influence of one's personal and family experience with vaccination, while the second factor represents the desire not to ask other parents about their experience with vaccination and their lack of interest in other parents' vaccination opinion. Conclusions. In light of its association with positive immunization- related outcomes, public health efforts should be directed to reinforce parents' empowerment.